Hydralazine Protects Nigrostriatal Dopaminergic Neurons From MPP+ and MPTP Induced Neurotoxicity: Roles of Nrf2-ARE Signaling Pathway - Guo, Xingfang; Han, Chao; Ma, Kai; Xia, Yun; Wan, Fang; Yin, Sijia; Kou, Liang; Sun, Yadi; Wu, Jiawei; Hu, Junjie; Huang, Jinsha; Xiong, Nian; et al. (Frontiers in Neurology, 2019)
Although the pathogenic mechanisms of Parkinson's disease (PD) remain unclear, ample empirical evidence suggests that oxidative stress is involved in the pathogenesis of this disease. The nuclear factor E2-related factor 2 (Nrf2) is known to activate several antioxidant response element (ARE)-driven antioxidative genes that prevents oxidative stress in vitro and in vivo. Moreover, it was documented that hydralazine is a potent Nrf2 activator. In this study, we tested whether hydralazine can attenuate 1-Methyl-4-phenylpyridinium (MPP+) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)- induced neurotoxicity in vitro and in vivo by activating Nrf2 and its downstream network of antioxidative genes. We found that treatment with hydralazine attenuated MPP+ or H2O2-induced loss of cell viability in human neuroblastoma cell line (SH-SY5Y). In addition, hydralazine significantly promoted the nuclear translocation of Nrf2, and upregulated the expression of its downstream antioxidative genes. Further, knockout of Nrf2 abolished the protection conferred by hydralazine on MPP+ -induced cell death. Similar findings were observed in vivo. Before, during, and after MPTP 30 mg/kg (i.p.) administration for 7 days, the mice were given hydralazine (Hyd) 51.7 mg/kg per day by oral gavage for 3 weeks. Oral administration of hydralazine ameliorated oxidative stress, MPTP-induced behavioral disorder, and loss of neurons of dopaminergic system in the substantia nigra (SN) and striatum, all of which were attributed to its ability to activate the Nrf2-ARE pathway. Hydralazine increased the migration of Nrf2 to the nucleus in dopaminergic neurons, enhanced the expression of its downstream antioxidative genes. Together, these datasets show that the Nrf2-ARE pathway mediates the protective effects of hydralazine on Parkinson's disease.